ЛАНДШАФТ-ГЕОХИМИЙН ДҮҮРЭГЧЛЭЛИЙН АСУУДАЛД (ЖАНЧИВЛАНГИЙН ДҮҮРГИЙН ЖИШЭЭН ДЭЭР ) - Г.УХНАА; П.НАРАНТУЯА (Geological Issues, 2023)
ЛАНДШАФТ-ГЕОХИМИЙН ДҮҮРЭГЧЛЭЛИЙН АСУУДАЛД (ЖАНЧИВЛАНГИЙН ДҮҮРГИЙН ЖИШЭЭН ДЭЭР )